2018
DOI: 10.20529/ijme.2018.057
|View full text |Cite
|
Sign up to set email alerts
|

RETRACTION: Increased incidence of cervical cancer in Sweden: Possible link with HPV vaccination

Abstract: The comment "Increased incidence of cervical cancer in Sweden: Possible link with HPV vaccination" (DOI: 10.20529/IJME.2018.037) was published online in the Indian Journal of Medical Ethics on April 30, 2018. The author gave his name and affiliation as Lars Andersson, department of Physiology and Pharmacology, Karolinska Institutet (KI), Sweden. On May 8, as soon as KI informed us that no such person worked there, we carried out a correction on the same day and the institution's name was removed as affiliation. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…It also confirmed that the author was competent to make the analysis published, and did face a "credible threat of harm", requiring protection of their identity.The article which was an analysis of a public database, requiring no special data access to be critiqued, remained on the journal website for some days. It was eventually retracted following extensive discussion among the members of the editorial board, on the grounds that "there should be zero tolerance to the author's deception, irrespective of the content of the paper" [1]. Its publication under a pseudonym had also received strong criticism in the academic community.…”
mentioning
confidence: 99%
“…It also confirmed that the author was competent to make the analysis published, and did face a "credible threat of harm", requiring protection of their identity.The article which was an analysis of a public database, requiring no special data access to be critiqued, remained on the journal website for some days. It was eventually retracted following extensive discussion among the members of the editorial board, on the grounds that "there should be zero tolerance to the author's deception, irrespective of the content of the paper" [1]. Its publication under a pseudonym had also received strong criticism in the academic community.…”
mentioning
confidence: 99%